Redesain Interior Restoran dan Toko Oleh-oleh Miraza Mey di Pandaan - Dewanda Geasantika Gunawan; Mariana Wibowo; Stephanie Melinda Frans (Intra, 2018)
Current development makes restaurant businesses become more promising, leads to many people started businesses in the field of food and beverages. The increasing amount of restaurant businesses drives the owners to think creatively in order to cultivate their restaurants in attracting visitors. Restaurant with a good potential will also have a great selling power. The chosen concept is Tulou with interior applications of geometry shapes, wood materials and a space concept that represent typical Tulou. Warm atmosphere is presented with the use of color gradations of brown and red as an accent that is typical of Miraza Mey restaurant. Meaningful symbols on furniture or interior elements trusted to bring good fortune to restaurant owners. The application of areas division concept will facilitate the activities in the restaurant. The design result are restaurant room, VIP room, kitchen, employee area, toilet and storage room designed by providing the required facilities.